2021
DOI: 10.1051/swsc/2021032
|View full text |Cite
|
Sign up to set email alerts
|

The operational and research DTM-2020 thermosphere models

Abstract: Aims - The semi-empirical Drag Temperature Models (DTM) predict temperature, density and composition of the Earth's thermosphere, especially for orbit computation purposes. Twonew models were developed in the framework of the H2020 Space Weather Atmosphere Models and Indices project (SWAMI). The operational model is driven by the trusted and established F10.7 and Kp indices for solar and geomagnetic activity, respectively. The so-called research model is more accurate, but it uses the indices F30 and the hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Uncertainties in density modeling can result in large discrepancies between expected and observed satellite positions (Bussy‐Virat et al., 2018; R. Licata et al., 2020, 2021). The most recent Drag Temperature Model (DTM‐2020) became the first prominent thermosphere model to provide uncertainty estimates (Bruinsma & Boniface, 2021). They determined 1‐ σ uncertainties as a function of the inputs (Boniface & Bruinsma, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties in density modeling can result in large discrepancies between expected and observed satellite positions (Bussy‐Virat et al., 2018; R. Licata et al., 2020, 2021). The most recent Drag Temperature Model (DTM‐2020) became the first prominent thermosphere model to provide uncertainty estimates (Bruinsma & Boniface, 2021). They determined 1‐ σ uncertainties as a function of the inputs (Boniface & Bruinsma, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The high‐cadence output of Hpo enables a more accurate selection of quiet‐time data than the three‐hourly Kp index. Bruinsma and Boniface (2021) used Hp60 to drive a recent version of the Drag Temperature Model, DTM‐2020, which is a semi‐empirical model of the Earth's thermosphere, developed for orbit determination and prediction of spacecraft and debris. They showed that the use of Hpo leads to the improvement of the model compared with the predecessor model DTM‐2013 (Bruinsma, 2015) that is driven by Kp .…”
Section: Discussionmentioning
confidence: 99%
“…Simulations using multiple empirical neutral atmosphere models including NRLMSISE‐00 (Picone et al., 2002, hereinafter referred as MSIS‐00), the updated version of MSIS‐00 model the NRLMSIS v2.0 (Emmert et al., 2021, hereinafter referred as MSIS v2.0), and Drag Temperature Model (DTM2020, Bruinsma & Boniface, 2021) are also examined. These empirical models describe atmospheric temperature, composition, and mass density based on various in‐situ or remote sensing observations of the neutral atmosphere.…”
Section: Numerical Models For Neutral Density Estimationsmentioning
confidence: 99%